Multisite analysis of patient experience scores and risk of hospital admission: a retrospective cohort study. Issue 1 (1st January 2023) - Hydoub, Yousif M.; Fischer, Karen M.; Hanson, Kristine T.; Coons, Trevor J.; Wilshusen, Laurie L.; Vista, Tafi L.; Colbenson, Gretchen A.; Burton, M. Caroline; Habermann, Elizabeth B.; Dugani, Sagar B.
ABSTRACT: Background: Routinely collected patient experience scores may inform risk of patient outcomes. The objective of the study was to evaluate the risk of hospital admission within 30-days following third-party receipt of the patient experience survey and guide interventions. Methods: In this retrospective cohort study, we analyzed Hospital Consumer Assessment of Healthcare Providers and Systems surveys, January 2016–July 2019, from an institution's 20 hospitals in four U.S. states. Surveys were routinely sent to patients using census sampling. We analyzed surveys received ≤60 days following discharge from patients living ≤60 miles of any of the institution's hospitals. The exposures were 19 survey items. The outcome was hospital admission within 30 days after third-party receipt of the survey. We evaluated the association of favorable (top-box) vs unfavorable (non–top-box) score for survey items with risk of 30-day hospital admission in models including patient and hospitalization characteristics and reported adjusted odds ratios (aOR [95% confidence interval]). Results: Among 40, 162 respondents (mean age ± standard deviation: 68.1 ± 14.0 years), 49.8% were women and 4.3% had 30-day hospital admission. Patients with 30-day hospital admission, compared to those not admitted, were more likely to be discharged from a medical service line (62.9% vs 42.3%; P < 0.001) and have a higher Elixhauser index. Favorable vs unfavorable score for hospital rating was associated with lower odds of 30-day hospital admission in the overall cohort (0.88 [0.77–0.99]; P = 0.04), medical service line (0.81 [0.70–0.94]; P = 0.007), and upper tertile of Elixhauser index (0.79 [0.67–0.92]; P = 0.003). Favorable score for recommend hospital was associated with lower odds of 30-day hospital admission in the medical service line (0.83 [0.71–0.97]; P = 0.02) but for others (e.g. cleanliness of hospital environment ) showed no association. Conclusion: In routinely collected patient experience scores, favorable hospital rating was associated with lower odds of 30-day hospital admission and may inform risk stratification and interventions. Evidence-based survey items linked to patient outcomes may also inform future surveys.